Optimum Management Of The T1 High Grade Bladder Cancer - Hossain, Md Abul; Islam, Md Waliul; Hooda, Md Nurul; Naser, Md Fazal; Azam, Md Shafiqul (Bangladesh Journal of Urology, 2020)
Objectives: To determine the optimum treatment option for patients with superficial high grade (T1Hg) bladder cancer. Introduction: Controversy exists about the most appropriate treatment for superficial high grade (T1Hg) bladder cancer. Immediate cystectomy offers the best chance for survival but associated with an impaired quality of life compared with conservative therapy. In case of conservative therapy lifelong surveillance is required and there is a high rate of recurrence and risk of disease progression. So optimum treatment option should be determined to treat the disease optimistically. Methods: A comprehensive and systemic search of the pubmed database for English Language articles was performed using the following medical subject Heading (MeSH): Bladder cancer, treatment of superficial high grade (T1Hg) bladder cancer, treatment options for bladder cancer, natural history of T1Hg bladder cancer, newer Intravesical agents, cystectomy and in addition reference of relevant articles were searched for additional references. Results: Approximately 70% of all newly diagnosed bladder tumors are non-muscle invasive bladder cancer. The management of these patients entails transurethral resection with or without adjuvant intravesical therapy. After review of obtained articles it is evident that the conservative treatment of T1Hg bladder cancer should be ended when there is systemic or local toxicity from intravesical therapy or patient is not complaint or persistence of tumor or tumor progression despite therapy. Conclusion : The management of T1Hg is highly variable due to several factors including divergence in treatment related evidence. The efficacy of treatments must be balanced with their toxicity, so that single treatment option cannot be considered superior across all Non-Muscle Invasive Bladder Cancer (NMIBC). Immediate radical cystectomy may be offered upfront in patients with T1Hg tumors with concomitant CIS or multiple recurrent high grade tumors. Bangladesh Journal of Urology, Vol. 16, No. 1, Jan 2013 p.26-32